2019
DOI: 10.1186/s12888-019-2131-6
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, metabolic disturbances and clinical correlates of recent suicide attempts in Chinese inpatients with major depressive disorder

Abstract: Background: Metabolic disturbances have been correlated with suicidality, but little is known about the association between suicide risk and metabolic disturbances among individuals with depression. This study was to evaluate the prevalence and clinical correlations, especially cardio-metabolic associated factors of recent suicide attempts in Chinese patients with major depressive disorder (MDD). Methods: A total of 288 MDD inpatients were recruited. Their clinical and demographic data together with plasma glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 52 publications
3
42
1
Order By: Relevance
“…In a study of 288 patients conducted by Ma et al [ 47 ], 20.14% had attempted suicide in the previous month. The authors found lower total cholesterol, and more symptoms of psychosis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a study of 288 patients conducted by Ma et al [ 47 ], 20.14% had attempted suicide in the previous month. The authors found lower total cholesterol, and more symptoms of psychosis.…”
Section: Resultsmentioning
confidence: 99%
“…Among others, Ma et al found a correlation between lower LDL-c and more psychotic symptoms showed [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-one studies [ 3 , 7 , 9 , 10 , 13 , 15 , 17 – 21 , 31 – 44 ], comprising a total of 6,775 patients with MDD, provided data on the serum TC concentrations of suicide attempters (2,560) and non-attempters (4,227) with MDD. The serum TC concentrations of suicide attempters with MDD were significantly lower than those of non-attempters (SMD: -0.63, 95% CI: -0.83 to -0.44, p < 0.001) ( Fig 2 , Table 2 ).…”
Section: Resultsmentioning
confidence: 99%